p. 6: http://www.math.uconn.edu/~kconrad/blurbs/grouptheory/gpaction.pdf enter image description here

Pretend the blue set was not given and I have to calculate it myself:
For all $x \in G, f(x) = xgH$ is faithful $\iff \color{blue}{\text{some set which I must find}} = \color{green}{\{id\}} $.

The PDF unfolds the answer: Because $ {g_2}^{-1}g_1 \in \color{blue}{\bigcap_{g \in G} gHg^{-1}} $, hence $ \color{blue}{\bigcap_{g \in G} gHg^{-1}} = \color{green}{\{id\}} $.

I tried: To determine the values of $ x $ for which $ f(x) = xgH$ is faithful, I solve $ g_1 * x = g_2 * x $. Here I let * represent the group binary operation.

$ g_1 * x = g_2 * x :\iff g_1(gH) = g_2(gH) \text{ for all } g \in G \iff g_2^{-1}g_1 \in \color{red}{gH}$.
The last $\iff$ is by dint of the result: ${ aH = bH \iff b^{-1}a \in H} $.

What did I bungle? I missed $\color{red}{\bigcap_{g \in G}}$ and $g^{-1}$?

  • $\begingroup$ Honestly I cannot follow your argument at all. What is $f$? Are $\{g_i\}$ some system of coset representatives? What does $g_1x=g_2x$ have to do with anything? Where is $x$ in the equation $f(g_i)=g_igH$? Note that $aH=bH\iff b^{-1}aH$ does not mean that $(g_1gH=g_2gH\forall g\in G)\implies g_2^{-1}g_1\in gH$ (this proposition doesn't even make sense, since $g$ is varying over $G$, and so the cosets are varying, whereas $g_2^{-1}g_1$ is fixed wrt $g$). $\endgroup$ – anon Dec 25 '12 at 19:26

It really doesn’t make sense to talk about the values of $x$ for which the action is faithful: faithfulness is a property of the action as a whole. I can’t make any sense of $$\implies g_2^{-1}g_1\;:$$ $g_2^{-1}g_1$ isn’t something that can be implies. It’s an element of the group $G$, not a statement.

Suppose that $\bigcap_{g\in G}gHg^{-1}=\{1_G\}$. In order to show that the action is faithful, you must show that if $g_1,g_2\in G$, and $g_1gH=g_2gH$ for all $g\in G$, then $g_1=g_2$. Now

$$\begin{align*} g_1gH=g_2gH\quad&\text{ iff }\quad g^{-1}g_2^{-1}g_1g\in H\\ &\text{ iff }\quad g_2^{-1}g_1\in gHg^{-1}\;, \end{align*}\tag{1}$$

so if $g_1gH=g_2gH$ for all $g\in G$, we must have

$$g_2^{-1}g_1\in\bigcap_{g\in G}gHg^{-1}\;.$$

If $\bigcap_{g\in G}gHg^{-1}=\{1_G\}$, this implies that $g_2^{-1}g_1=1_G$ and hence that $g_1=g_2$, as desired.

Conversely, suppose that $\bigcap_{g\in G}gHg^{-1}\ne\{1_G\}$, and fix $g_1\in\bigcap_{g\in G}gHg^{-1}$ with $g_1\ne 1_G$. Let $g_2=1_G$; you can reverse the calculations above to show that $g_1gH=g_2gH$ for all $g\in G$ and hence that the action is not faithful: $g_1$ and $1_G$ act identically on $G/H$.

| cite | improve this answer | |
  • $\begingroup$ @Frank: I started from it, but as I said at the end, the argument can be reversed to find it. To see how your calculation should have gone, look at $(1)$ above; I’m not sure what you were thinking when you concluded that $g_2^{-1}g_1\in gH$. $\endgroup$ – Brian M. Scott Dec 25 '12 at 20:33
  • $\begingroup$ Thank you. Sorry for the confusion, but the question actually asks us to find $ \color{blue}{\bigcap_{g \in G} gHg^{-1}} $ on our own. Although it was quick to prove $ g^{-1}ug \in H \iff u \in gHg^{-1} \forall u \in G$, I don't see how you'd realize that you'd need this property? I understand (1) after looking at the answer and your work, but if I didn't know what the answer was, I wouldn't know to do $$ g^{-1}{g_2}^{-1}g_1g \in H \iff g_2^{-1}g_1 \in gHg^{-1}.$$ How would you know to do this in the forward step? $\endgroup$ – Group Theory Dec 25 '12 at 20:36
  • $\begingroup$ @Frank: I just asked myself what it meant to have $g_1gH=g_2gH$ for all $g\in G$ and discovered immediately that this was equivalent to $g^{-1}g_2^{-1}g_1g\in H$ for all $g\in G$. The $g^{-1}g_2^{-1}g_1g$ is a conjugate of $g_2^{-1}g_1$, and $H$ is normal, so I immediately think of moving the $g$ factors to the other side: $g_2^{-1}g_1\in gHg^{-1}$ for all $g\in G$. And that tells me that $g_1$ and $g_2$ act identically on $G/H$ iff $g_2^{-1}g_1$ is in the intersection of all the conjugates of $H$, which is a fairly natural object. $\endgroup$ – Brian M. Scott Dec 25 '12 at 20:41
  • $\begingroup$ Thank you so much again. Two last inquiries: (3) What didn't make sense about $ \implies {g_2}^{-1}g_1 \in gH $? I'm just using $ aH = bH \implies b^{-1}a \in H $? (4) I still don't see how to realize that I need the intersection. I know the meaning of it --- we want to emphasize that $ {g_2}^{-1}g_1 \in \text{ all of the } gHg^{-1} $. But at the start, we already said $ \forall g \in G $. Isn't this sufficient? Why add on the intersection sign at the end? $\endgroup$ – Group Theory Dec 25 '12 at 21:04
  • $\begingroup$ @Frank: (3) I didn’t see the $\in gH$: in the original post the $g_2^{-1}g_1$ was at the end of short line and was followed by a full stop, so I took it to be the end of the sentence. (4) It’s not a matter of emphasizing anything: we’ve discovered that $g_1$ and $g_2$ act identically on $G/H$ iff $g_2^{-1}g_1\in gHg^{-1}$ for every $g\in G$, and $g_2^{-1}g_1\in\bigcap_{g\in G}gHg^{-1}$ is simply a shorter way of saying that $g_2^{-1}g_1\in gHg^{-1}$ for every $g\in G$. I’m really not sure what your confusion here is. $\endgroup$ – Brian M. Scott Dec 25 '12 at 21:14

The group action is faithful if the action of an element $x$ is trivial iff $x=1_G$. That is, if

$$(xgH=gH\text{ for each }g\in G)\iff x=e $$

Of course, the condition $xgH=gH$ can be rewritten as

$$g^{-1}xgH=H\iff g^{-1}xg\in H\iff x\in gHg^{-1}.$$

Is the path forward clear now?

| cite | improve this answer | |
  • $\begingroup$ Thanks anon. I fixed some notation. but for what values of $ x $ is it true that $axH = bxH \text{ for all } x \in G \iff b^{-1}a \in xH $? I thought $ aH = bH \iff b^{-1}a \in H $ implied this. $\endgroup$ – Group Theory Dec 25 '12 at 20:26
  • $\begingroup$ @Frank: How can you have $\forall x$ on the left of the iff sign, and another $x$ on the right? What does that even mean? How can $b^{-1}a\in x_1H$ and $b^{-1}aH\in x_2H$ when (say) $x_1H$ and $x_2H$ happen to be disjoint cosets (answer: it's impossible). It further doesn't make sense to ask "for what values of $x$" makes a $\forall x$ statement true. Please reflect on what "for all $x$" means. In the statement $aH=bH\iff b^{-1}a\in H$, you cannot replace the subgroup $H$ with some coset $xH$ of $H$ - why are you convinced that works? Do you know why $b^{-1}aH=H$ implies $b^{-1}a\in H$? $\endgroup$ – anon Dec 26 '12 at 1:14

The action is faithful iff

$$\left(\forall\,x\in G\,\,,\,g(xH)=xH\Longleftrightarrow g=1\right)\Longleftrightarrow \left(\forall\,x\in G\,\,,\,gxH=xH\Longleftrightarrow g=1\right)$$

$$\Longleftrightarrow \,\,\left(\forall\,x\in G\,\,,\,x^{-1}gx\in H\Longleftrightarrow g= 1\right)\,\Longleftrightarrow \,\,\forall\,x\in G\,\,,\,g\in xHx^{-1}=1$$

| cite | improve this answer | |

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.